Atlas of great comets - Stoyan, Ronald (Cambridge University Press, 2015)
Throughout the ages, comets, enigmatic and beautiful wandering objects that appear for weeks or months, have alternately fascinated and terrified humankind. The result of five years of careful research, Atlas of Great Comets is a generously illustrated reference on thirty of the greatest comets that have been witnessed and documented since the Middle Ages. Special attention is given to the cultural and scientific impact of each appearance, supported by a wealth of images, from woodcuts, engravings, historical paintings and artifacts, to a showcase of the best astronomical photos and images. Following the introduction, giving the broad historical context and a modern scientific interpretation, the Great Comets feature in chronological order. For each, there is a contemporary description of its appearance along with its scientific, cultural and historical significance. Whether you are an armchair astronomer or a seasoned comet-chaser, this spectacular reference deserves a place on your shelf
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte; Comets / Popular works; Comets / Pictorial works; Komet; Bildband